2019
DOI: 10.2176/nmc.tn.2019-0025
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of a New Electronic Conductivity Device with a Pedicle Probe and a Multi-axis Angiography Unit for Inserting a C1 Lateral Mass Screw Safely and Tightly: A Technical Note

Abstract: The C1 lateral mass screw (LMS) is widely used as one of the screws for atlantoaxial fixation. Tight bicortical screwing from the posterior to anterior cortical margin of the atlas is recommended. However, important structures, such as the internal carotid artery, are located around this area so precision is required to avoid injuring them. We describe the usefulness of a new electronic conductivity device (ECD) with a pedicle probe and a multi-axis angiography unit for inserting the C1 LMS. Four consecutive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“… 16) Chaput et al reported that pedicle screw placement with ECD guidance was accurate and decreased irradiation levels in clinical practice. 17) Other studies have also shown the accuracy of screw placement, even for the placement of cervical pedicle screws in children, 23) C1 lateral mass screws, 24) and S2 alar iliac screws. 25) Thus, since 2005, when the ECD was released, many studies have reported the efficiency of screw insertion using ECD in spinal surgery.…”
Section: Discussionmentioning
confidence: 97%
“… 16) Chaput et al reported that pedicle screw placement with ECD guidance was accurate and decreased irradiation levels in clinical practice. 17) Other studies have also shown the accuracy of screw placement, even for the placement of cervical pedicle screws in children, 23) C1 lateral mass screws, 24) and S2 alar iliac screws. 25) Thus, since 2005, when the ECD was released, many studies have reported the efficiency of screw insertion using ECD in spinal surgery.…”
Section: Discussionmentioning
confidence: 97%
“…New applications and techniques have been designed for ECD. Besides the percutaneous transpedicular puncture in patients with vertebral compression fractures, 19 Kageyama et al 39 found ECD was useful for an optimal positioning of bi-cortical screws in the lateral mass of C1 atlas. Sandhu et al 40 used ECD in sacro-iliac screw and found 100% stable and accurate fixation.…”
Section: Safety and Effectiveness Of The Modified Ecd Withmentioning
confidence: 99%